2019
DOI: 10.1364/boe.10.003584
|View full text |Cite
|
Sign up to set email alerts
|

In vivo terahertz imaging to evaluate scar treatment strategies: silicone gel sheeting

Abstract: Silicone gel sheeting (SGS) is widely used for scar treatment; however, studies showing its interaction with skin and efficacy of scar treatment are still lacking. THz light is non-ionizing and highly sensitive to changes in water content and thus skin hydration. In this work, we use in-vivo THz imaging to monitor how SGS affects the THz response of human skin during occlusion, and the associated THz reflectivity and refractive index changes are presented. We find that SGS effectively hydrates the skin beneath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
(34 reference statements)
0
26
0
Order By: Relevance
“…Silicone gel treatment and intralesional injection of immunomodulatory drugs have recently emerged as the most promising treatment regimens, with high quality, randomized, (placebo‐)controlled studies, still being scarce. The exact mechanism of action of silicone sheeting is still inconclusive; increased temperature, 18 increased hydration, 19 polarized electric charge leading to scar shrinking, 20 and others are being discussed 21,22 . The mechanisms of immunomodulatory drugs are studied more intensively.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone gel treatment and intralesional injection of immunomodulatory drugs have recently emerged as the most promising treatment regimens, with high quality, randomized, (placebo‐)controlled studies, still being scarce. The exact mechanism of action of silicone sheeting is still inconclusive; increased temperature, 18 increased hydration, 19 polarized electric charge leading to scar shrinking, 20 and others are being discussed 21,22 . The mechanisms of immunomodulatory drugs are studied more intensively.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid progress in terahertz (THz) optoelectronics observed during the past few decades [1][2][3][4] stimulates research in the area of THz biophotonics, [5] with an emphasis on the label-free medical diagnosis of malignant and benign neoplasms, [6,7] evaluation of scar treatment strategies, [8] sensing of glycated tissues and blood, [9] studying hydration, [10] viability [11] and injuries [12] of tissues. For example, most recently, an ability for differentiation between intact brain tissues and gliomas of WHO different grades (here, WHO stands for the World Health Organization) was demonstrated in refs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its non-invasive and non-ionizing nature, THz imaging is desirable for in vivo human diagnosis and monitoring. Research has shown that THz imaging is able to evaluate the water content of skin in vivo [ 2 , 3 ]. Hernandez-Cardoso et al demonstrated that due to water content changes, THz imaging can be used to detect early signs of vascular deterioration caused by diabetic foot syndrome [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hernandez-Cardoso et al demonstrated that due to water content changes, THz imaging can be used to detect early signs of vascular deterioration caused by diabetic foot syndrome [ 4 ]. Wang et al used THz imaging to monitor the effect of silicone gel on human skin and proved that THz radiation can be used for real-time monitoring of treatment efficiency [ 2 ]. Other work including burn scar imaging and corneal hydration sensing have also attracted interest for investigation with THz radiation [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%